Plant Cold Hardiness From the Laboratory to the Field - Gusta, Lawrence V (CABI, 2014)
This book is a collection of invited and selected papers on plant cold hardiness that were presented at the 8 th International Plant Cold Hardiness Seminar (8IPCHS) hosted by the University of Saskatchewan (U of S) in August 3–9, 2007. It began at the U of S in time for our campus’ 100 th anniversary. On the third day, the entire conference moved northward to the edge of the boreal forest at Elk Ridge Resort, Waskesiu, Saskatchewan. There were over 105 attendees representing 22 countries. The theme of the conference was: ‘From the Laboratory to the Field’. The collection of chapters in this book represent many of the topics that were presented during the conference. The conference and the book sought to integrate the most up to date basic and applied research on plant cold hardiness. Attendees at the conference included molecular biologists, plant physiologists, plant breeders, plant ecologists, microbiologists, agronomists, administrators, policy makers, and representatives from multinational companies. Due to the structure of the conference, scientists and students had ample time to personally discuss their research with colleagues and in many cases formulate collaborative research plans. The conference provided a better understanding of the stresses plants experience under field conditions compared to analyzing plants in a greenhouse, laboratory, or growth chamber. It also made applied researchers aware of new technologies to study freezing in plants.